Beta-glucuronidase chemiluminescent probe as well as preparation method and application thereof - ZHANG LING; YING WEIWU; BAO ZIHAO; LYU LI; SHI YIFAN; FENG AILU; XUE YUNSHENG (2023)
The invention belongs to the field of chemical and biological detection, and particularly relates to a beta-glucuronidase chemiluminescent probe as well as a preparation method and application thereof. The chemiluminescent probe has a chemical structure as shown in a formula (I). The near-infrared chemiluminescence probe for detecting the beta-glucuronidase is provided for the first time, the probe is stable in property, the selectivity is good when the beta-glucuronidase is detected, the detection limit is low (0.128 U/L), and fluorescence and chemiluminescence imaging detection of the beta-glucuronidase in human breast cancer cells MCF-7 is achieved. And in a breast cancer nude mouse subjected to MCF-7 xenotransplantation, the probe can also realize chemiluminescence imaging detection of beta-glucuronidase at a living body level. The probe CL-GLU can be used for quantitatively detecting the enzyme activity level of beta-glucuronidase in human plasma. 本发明属于化学和生物检测领域，具体涉及一种β-葡萄糖醛酸苷酶化学发光探针及其制备方法和应用。该化学发光探针具有式(